Is There a Bidirectional Causal Relationship Between Religiosity and Volunteering? - Son, Joonmo (Journal for the scientific study of religion, 2021)
Most studies of the effect of religiosity on volunteering overlook or fail to deal adequately with the possibility that there is reverse causal relation, from volunteering to religiosity, which should be taken into account. Using four waves of the Americans’ Changing Lives study, we estimate a reciprocal relationship between church attendance and religious and secular volunteering, using dynamic panel models with fixed effects using structural equation modeling and measuring both lagged and proximate effects. Religious service attendance increases future religious volunteering via its proximate effect on religious volunteering while religious volunteering has cross-lagged and proximate effects on both religious service attendance and secular volunteering. On the other hand, there are neither cross-lagged nor proximate effects between church going and secular volunteering. Religious and secular types of volunteering are reciprocally related, suggesting religious people are drawn into secular work not only directly, but also via their volunteer work for religious organizations.